NON-DIABETIC MATERNAL FACTOR WITH CAUDAL REGRESSION SYNDROME – A NOVEL CASE REPORT - DIVYA JAMES FENN; V.BALACHANDAR; K.SARASWATHI; S.M.PRIYADHARSHINI (International Journal of Pharma and Bio Sciences, 2015)
Caudal regression syndrome (CRS) is a rare neural tube defect which impairs thedevelopment of lower (caudal) half of the body. The spectrum of this disease can vary from isolated partialgenesis of the sacrococcygeal spine to complete absence of sacral, lumbar, or lower thoracic vertebrae. Most of the cases which are reported as the causative agent for CRS are mostly due to a diabetic maternal pattern. But there are few cases of CRS which are seen occurring even when there is no maternal diabetes or any genetic pre-disposition or influence from any kind of teratogens. Thus here we are discussing a unique case of a new born deceased infant with CRS with a clear background,that is a non-diabetic mother and no inheritance from the hereditary. We have also done karyotyping from the peripheral blood of the new born infant to identify thechromosomal anomalies which have been allied with this syndrome. Thus these preliminary as well as novel findings are beginning to shed light on this very rare syndrome in which further more researches have to be carried out to uncover the actual pathogenesis linked to this syndrome.